Genetic and epigenetic variation in transposable element expression responses to abiotic stress in maize. Issue 1 (16th February 2021) - Liang, Zhikai; Anderson, Sarah N; Noshay, Jaclyn M; Crisp, Peter A; Enders, Tara A; Springer, Nathan M
Abstract: Transposable elements (TEs) pervade most eukaryotic genomes. The repetitive nature of TEs complicates the analysis of their expression. Evaluation of the expression of both TE families (using unique and multi-mapping reads) and specific elements (using uniquely mapping reads) in leaf tissue of three maize ( Zea mays ) inbred lines subjected to heat or cold stress reveals no evidence for genome-wide activation of TEs; however, some specific TE families generate transcripts only in stress conditions. There is substantial variation for which TE families exhibit stress-responsive expression in the different genotypes. In order to understand the factors that drive expression of TEs, we focused on a subset of families in which we could monitor expression of individual elements. The stress-responsive activation of a TE family can often be attributed to a small number of elements in the family that contains regions lacking DNA methylation. Comparisons of the expression of TEs in different genotypes revealed both genetic and epigenetic variation. Many of the specific TEs that are activated in stress in one inbred are not present in the other inbred, explaining the lack of activation. Among the elements that are shared in both genomes but only expressed in one genotype, we found that many exhibit differences in DNA methylation such that the genotype without expression is fully methylated. This study provides insights into the regulation of expression of TEs in normal and stress conditions and highlights the role of chromatin variation between elements in a family or between genotypes for contributing to expression variation. The highly repetitive nature of many TEs complicates the analysis of their expression. Although most TEs are not expressed, some exhibits expression in certain tissues or conditions. We monitored the expression of both TE families (using unique and multi-mapping reads) and specific elements (using uniquely mapping reads) in leaf tissue of three maize ( Zea mays ) inbred lines subjected to heat or cold stress. While genome-wide activation of TEs did not occur, some TE families generated transcripts only in stress conditions with variation by genotype. To better understand the factors that drive expression of TEs, we focused on a subset of families in which we could monitor expression of individual elements. In most cases, stress-responsive activation of a TE family was attributed to a small number of elements in the family. The elements that contained small regions lacking DNA methylation regions showed enriched expression while fully methylated elements were rarely expressed in control or stress conditions. The cause of varied expression in the different genotypes was due to both genetic and epigenetic variation. Many specific TEs activated by stress in one inbred were not present in the other inbred. Among the elements shared in both genomes, full methylation inhibited expression in one of the genotypes. This study provides insights into the regulation of TE expression in normal and stress conditions and highlights the role of chromatin variation between elements in a family or between genotypes for contributing to expression. Abstract : Transposable elements exhibit variable responses to abiotic stress within transposon families and between genotypes due to both genetic and epigenetic variation. 2